Effect of soil properties irrigated with water contaminated with heavy elements and methods of treatment - Hanan Abdel Wahab Saeed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Many properties of soil irrigated with contaminated water affect the readiness of heavy elements, including (Ni, Cd, Pb, Zn), whose concentrations and harmful can be reduced and and accumulation in the soil can be reduced by using natural materials, including agricultural plant residues and some mineral materials used in soil and water treatment and reuse. For irrigation purposes and rational use of water resources.